The Gambling Motives Questionnaire financial: factor structure, measurement invariance, and relationships with gambling behaviour. Issue 1 (2nd January 2016) - Schellenberg, Benjamin J. I.; McGrath, Daniel S.; Dechant, Kristianne
Abstract: Items assessing financial motives were recently integrated with the Gambling Motives Questionnaire (GMQ), resulting in a revised measure that assesses coping, enhancement, social and financial motives for gambling (GMQ-F). The aim of this research was to test the proposed four-factor structure of the GMQ-F, determine if GMQ-F responses were invariant across sex, and test a structural model that specifies links between motives, gambling frequency and problem gambling severity. Telephone surveys were conducted with 932 adult gamblers from across Manitoba, Canada, who responded to items from the GMQ-F and reported their frequency of gambling and levels of problem gambling severity. Confirmatory factor analysis yielded strong support for the four-factor structure of GMQ-F scores, and invariance testing provided evidence of measurement invariance across sex. Finally, support was found for the hypothesized structural model in which each gambling motive predicted gambling frequency, which in turn predicted problem gambling severity. Coping motives also directly predicted problem gambling severity. These results provide strong evidence in support of the validity of GMQ-F responses, offer further support for the integration of financial motives with the GMQ, and delineate relationships between gambling motives, gambling frequency and gambling-related harm.